Parental Knowledge of AAP Juice Guidelines Is Associated With Parent and Children's Consumption of Juice and Sugar-Sweetened Beverages in an Underserved Population. (February 2018) - SanGiovanni, Christine; Fallar, Robert; Green, Robert; Mogilner, Leora
This study tested whether parental knowledge of the American Academy of Pediatrics' (AAP) recommendations on juice limits for children is associated with decreased consumption of juice and sugar-sweetened beverages (SSBs) among parents and children. Fifty-two parents with children 2 to 12 years old in a resident continuity clinic in East Harlem, New York, completed a survey asking about children's and parent's practice and quantitative consumption of juice and SSBs as well as parental knowledge of the AAP recommendations on juice limits. Parent's total daily consumption of juice and SSBs ( P < .01), parent's score on the test of AAP guidelines ( P = .04), and parent's post–high school education ( P = .01) were associated with children's juice and SSB consumption in a multivariable linear regression model. Children's consumption of juice and SSBs is positively associated with parental consumption of juice and SSBs and negatively associated with parental formal education and knowledge of the AAP recommendations on juice limits.